Centrifuge and numerical modelling of the seismic response of tunnels in two-layered soils. (July 2021) - Zhou, Haizuo; Xu, Huajun; Yang, Pengbo; Zheng, Gang; Liu, Xiangning; Zhang, Wenbin; Zhao, Jiapeng; Yu, Xiaoxuan
Highlights: Discussed the seismic performance of tunnels located in various soil deposits. Analyzed the seismic characteristics between free and structural fields. Compared the dynamic lining forces of tunnels with analytical solutions. Abstract: Soil deposits inevitably affect the seismic performance of underground structures, and underground tunnels are commonly constructed on sites composed of layered soil deposits. In this study, dynamic centrifuge tests and numerical modelling are conducted to enhance the fundamental understanding of the kinematic soil-tunnel interaction for tunnels constructed in layered soils that consist of muddy clay and silty clay. The site seismic response and tunnel seismic performance between the centrifuge and numerical modelling are compared. The acceleration time histories, amplification factors of the input motions, and the Fourier spectra between free field and structural field are experimentally and numerically investigated. For comparative purposes, parametric studies of tunnels in a single muddy clay and a single silty clay using verified numerical modelling are carried out. In addition, the dynamic bending moment and axial forces obtained by centrifuge and numerical modelling are compared with the solutions predicted by analytical methods in prior studies.